Hydroalumination of Oligoalkynylgermanes and ‐digermanes – Reactions with Heterocumulenes by Al–C or Ge–C Bond Activation and Formation of a Hexazenedialuminum Complex. Issue 17 (24th May 2018) - Uhl, Werner; Honacker, Christian; Lawrence, Neil; Hepp, Alexander; Schürmann, Lina; Layh, Marcus
Abstract : Hydroalumination of the dialkynylgermane Ph2 Ge(C≡C t Bu)2 (1 ) and the digermanes Ph n ( t BuC≡C)3– n Ge–Ge(C≡C t Bu)3– n Ph n (2a : n = 2;2b : n = 1) with two equivalents of H–Al t Bu2 or H–AlEt2 yielded the mixed Al/Ge compounds Ph2 Ge[C(Al t Bu2 )=CH‐ t Bu]2 (3 ), [Ph2 GeC(Al t Bu2 )=CH‐ t Bu]2 (4a ), and [Ph2 GeC(AlEt2 )=CH‐ t Bu]2 (4b ). Reactions of2b with both aluminum hydrides afforded inseparable mixtures of products.3 reacted with heterocumulenes by retrohydroalumination. Phenyl isocyanate gave insertion of the C=N group into the resulting Ge–C(≡C– t Bu) bond (5 ), whereas the NCS and NCN groups of phenyl isothiocyanate and a carbodiimide inserted into Al–Cvinyl bonds (6 and7 ) with unaffected terminal Ge–C≡C– t Bu moieties. The generation of5 represents the first example of the insertion of a heterocumulene into a Ge–C bond, which may be favored by the activation of the isocyanate group by the Lewis acidic Al atom and the increased polarity of the N=C=O fragment as determined by NBO calculations. The reactions of the digermanes4 with heterocumulenes were unselective and afforded inseparable mixtures. Treatment of4a with the azide (4‐ t Bu)C6 H4 CH2 –N3 led interestingly to reductive coupling of two azide molecules, and the hexazene complex ( t BuC6 H4 CH2 N3 –N3 C6 H4 t Bu)(Al t Bu2 )2 (8 ) was isolated in moderate yield. Six nitrogen atoms form a dianionic chain, which coordinated two Al t Bu2 fragments by formation of two joint AlN4 heterocycles. Abstract :